Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
DOI: 10.14264/uql.2018.555
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal growth in cattle in response to nutritional and hormonal manipulation

Abstract: Poppi., DP 2016, ' Metabolisable energy intake but not crude protein intake or bovine somatotropin hormone (bST) increased hip height in Bos indicus cross steers. ', in 31st

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 366 publications
(475 reference statements)
0
3
1
Order By: Relevance
“…The hip height gain was not different between treatments (P=0.19; Table 2). The HH gain was slightly lower than that was reported by Antari, (2018) in Brahman-cross steers at the same age (85 mm/100 d). Our results showed that the bulls still grew taller but at a slower rate than the previous study, the differences were probably because of the nutritional content of the diet offered to the cattle and the breed.…”
Section: Intakes Liveweight Gain Hip Height Gain and Body Condition S...contrasting
confidence: 72%
See 3 more Smart Citations
“…The hip height gain was not different between treatments (P=0.19; Table 2). The HH gain was slightly lower than that was reported by Antari, (2018) in Brahman-cross steers at the same age (85 mm/100 d). Our results showed that the bulls still grew taller but at a slower rate than the previous study, the differences were probably because of the nutritional content of the diet offered to the cattle and the breed.…”
Section: Intakes Liveweight Gain Hip Height Gain and Body Condition S...contrasting
confidence: 72%
“…Plasma glucose, triglyceride, low-density lipoprotein (LDL), high-density lipoprotein (HDL) of Ongole crossbred bulls offered supplements containing protected calcium salts of fatty acid-amino acid at null (A), 0.3 g/kg LW (B) and 0.6 g/kg LW. (Antari, 2018), the eye muscle areas was around 68 cm 2 , the discrepancy of the results probably because of breed differences and feed type offered to the cattle. Thus, the depth of the muscle was likely affected by the basal diet offered to the bulls.…”
Section: The Fat Depth and Muscle Depthmentioning
confidence: 83%
See 2 more Smart Citations
“…The greater measurements in males may be due to physiological factors like hormonal secretions and sexspecific activities, as suggested by Callewaert (2010) and Antari (2018). These higher values could also be linked to body size and the observed sexual dimorphism in cranial Osteo-morphometric Approach to the Heads of Dromedaries (Camelus dromedarius, L, 1758): Case of the Algerian Targui Population m easu rem en ts m igh t b e p ro p ortio n ate to size differen ces, c onsistent with observations made by Cardini and Eltonw (2008).…”
Section: Sexual Dimorphism Index (Ds)mentioning
confidence: 99%